Trajectories of antipsychotic response in drug‐naive schizophrenia patients: results from the 6‐month ESPASS follow‐up study. (18th April 2013) - Nordon, C.; Rouillon, F.; Azorin, J. M.; Barry, C.; Urbach, M.; Falissard, B.
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to explore any heterogeneity in the 6‐month clinical response in patients with antipsychotic drug‐naive schizophrenia and to determine predictors of that outcome. Method 467 patients with antipsychotic drug‐naive schizophrenia were included in France nationwide and followed up over 6 months. To identify trajectories of clinical response, a latent class growth analysis (LCGA) was performed using the Clinical Global Impression‐Severity (CGI‐S) scores at baseline, 1, 3, and 6 months. Regression models were used to identify predictors of trajectory membership. Results Five trajectory groups were identified: a rapid response group (n = 45), a gradual response group (n = 204), patients remaining mildly ill (n = 133), patients remaining very ill (n = 23), and a group with unsustained clinical response (n = 62). Predictors of the 6‐month clinical response were baseline CGI‐S score (odds ratio: 3.1; 95% confidence interval, 2.1–4.4) and negative symptoms (OR, 1.5; 95% CI, 1.2–1.9). The sole predictor of rapid response as compared to gradual response was employment (OR, 2.5; 95% CI, 1.2–4.9). Conclusion Clinical response in patients with schizophrenia 6 months after a first‐ever antipsychotic drug initiation is heterogeneous. Therapeutic strategies in first episode should take account of symptom severity and early clinical response, to maximize the chances of recovery.